OPTIMASI ALAT BERAT EXCAVATOR PADA REHABILITASI SALURAN IRIGASI PRIMER UTAMA BLOK A KAPUAS: - dwi kuryanto, totok; Galuh, Senki Desta (Universitas Muhammadiyah Jember, 2023)
Construction equipment, particularly the expertise of heavy equipment mechanics, plays a pivotal role in the implementation of construction projects. Beyond simply reducing the required labor force, mechanical heavy equipment also ensures a more expeditious completion of tasks. When choosing heavy equipment, it is imperative to align it with the specific requirements of the construction work, considering the equipment's efficiency. The refurbishment of the food estate irrigation network situated in Dadhub subdistrict, Kuala Kapuas district, constitutes a construction undertaking that necessitates the use of heavy equipment. Consequently, effective management of time and costs associated with utilizing heavy equipment is crucial for this activity. The objective of this research is to scrutinize the optimal combination of heavy equipment concerning the execution time for excavation and landfill tasks, aiming to mitigate losses incurred due to project delays. The research methodology employed involves the calculation of production capacity and time efficiency for each heavy equipment type. The analysis results reveal a cycle time coefficient of 0.6, an hourly productivity of 28.26 m3, and a daily productivity of 226.08 m3. If heavy equipment is utilized, the results indicate the capability to accomplish the excavation of 148,200 m3 within 655.46 days. By incorporating three additional tools, bringing the total to four tools, the excavation work can be finalized in 163.88 days under prevailing conditions.